PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA AUDITOR (Studi Empiris Pada Auditor KAP di Kota Semarang) - Rengganis, Fany Dewi; Isgiyarta, Jaka (Diponegoro Journal of Accounting, 2015)
This research aims to examine the effect of the information technology application to auditor’s performance. This research is a replication of the research that has been done by Herusetya (2011) with differences in sample, variables and analysis method due to data resource differences. This study used primary data taken from accountant public firm in Semarang, while the previous research used primary data taken from the Big Four public accountant firm. There are totally respondents of 46 auditors who work in the public accountant firm in Semarang used in this study. Data analysis method that has been used is multiple regression analysis with statistical programs IBM SPSS 21. This research is expected to measure the application of information technologi including skill and knowledge of the auditor in information technology, system usage,perceived usefulness and its effect to auditor’s performance. The result of this research indicates that the application of information technology which is represented by three independent variables, skill and knowledge, system usage and perceived usefulness, has a positive and significant influence about the auditor’s performance. The findings of this study recommends increased in information technology usage so that the effectiveness and efficiency of the audit process can be improved